Multisite Infection with Mycobacterium abscessus after Replacement of Breast Implants and Gluteal Lipofilling - Eva Rüegg; Alexandre Cheretakis; Ali Modarressi; Stephan Harbarth; Brigitte Pittet-Cuénod (Case Reports in Infectious Diseases)
Introduction. Medical tourism for aesthetic surgery is popular. Nontuberculous mycobacteria (NTM) occasionally cause surgical-site infections. As NTM grow in biofilms, implantations of foreign bodies are at risk. Due to late manifestation, infections occur when patients are back home, where they must be managed properly. Case Report. A 39-year-old healthy female was referred for acute infection of the right gluteal area. Five months before, she had breast implants replacement, abdominal liposuction, and gluteal lipofilling in Mexico. Three months postoperatively, implants were removed for NTM-infection in Switzerland. Adequate antibiotic treatment was stopped after seven days for drug-related hepatitis. At entrance, gluteal puncture for bacterial analysis was performed. MRI showed large subcutaneous collection. Debridement under general anaesthesia was followed by open wound management. Total antibiotic treatment was 20 weeks. Methods. Bacterial analysis of periprosthetic and gluteal liquids included Gram-stain plus acid-fast stain, and aerobic, anaerobic and mycobacterial cultures.  Results. In periprosthetic fluid, Mycobacterium abscessus, Propionibacterium, and Staphylococcus epidermidis were identified. The same M. abscessus strain was found gluteally. The gluteal wound healed within six weeks. At ten months’ follow-up, gluteal asymmetry persists for deep scarring. Conclusion. This case presents major complications of multisite aesthetic surgery. Surgical-site infections in context of medical tourism need appropriate bacteriological investigations, considering potential NTM-infections.